PENGARUH TOTAL ASSET TURNOVER, SALES GROWTH, DEBT TO EQUITY, CURRENT RATIO TERHADAP RETURN ON ASSET PADA PERUSAHAAN INDUSTRI DASAR DAN KIMIA DI BURSA EFEK INDONESIA PERIODE 2013-2016 - Napitupulu, Elisabet; Febrianti, Hosana Rohama; Marbun, Rasroyama Elena; Malau, Yois Nelsari (Aksara Public, 2019)
The purpose of this study is to test and analyze the effect of total asset turnover, sales growth, debt to equity ratio, current ratio to return on assets in the period 2013-2016. The independent variable used in this study is total asset turnover, sales growth, debt to equity ratio, current ratio, while the dependent variable is return on assets. The population used in this study amounted to 69 companies by taking financial report data that existed in basic and chemical industry companies on the Indonesia Stock Exchange. The research sample was taken using purposive sampling obtained as many as 31 samples. This study uses a quantitative approach, the type of descriptive research, the nature of research on causal relationships. Data collection techniques with documentation techniques. The test of statistical analysis used is classic asumi test, multiple linear analysis research model, and coefficient of determination using simultaneous test and partial test in the table of significant values ​​of 0.05. The results of this study indicate partially total asset turnover and debt to equity ratio does not have a positive and insignificant effect on return on assets, while sales growth and current ratio partially have a positive and significant effect on return on assets. Simultaneously, total asset turnover, sales growth, debt to equity ratio, current ratio has an effect on and significant to return on assets. The Adjusted R Square test results show 30.7% of the variation of the dependent return on assets variables which can be explained by total asset turnover, sales growth, debt to equity ratio, current ratio while the remaining 69.3% is explained by other variables not explained in the study such as company size, working capital, inventory turnover.